2009
DOI: 10.1016/j.tetlet.2009.09.147
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of Bakuchiol using diazosulfonate C–H insertion to install the quaternary center

Abstract: Bakuchiol was prepared from commercial (−)-citronellol using the diazosulfonate C-H insertion to control the regioselectivity and install the quaternary center.We recently reported a modification of C-H insertion that permits assembly of six-membered sulfur-containing heterocycles, 1 effectively introducing substitution at a remote position to an existing functionality. The synthetic potential of this reaction has yet to be demonstrated. In this report we describe an application of this methodology for constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…The first enantiocontrolled synthesis of 190 was completed by starting from (S)-O-benzylglycidol [109] . Later, several simple and convenient methods were reported for the total synthesis of 190 [110][111][112][113][114] . A study on the constituents of the mangrove plant Lumnitzera racemosa produced two alkylphenols 191 and 192 [115] .…”
Section: Miscellaneousmentioning
confidence: 99%
“…The first enantiocontrolled synthesis of 190 was completed by starting from (S)-O-benzylglycidol [109] . Later, several simple and convenient methods were reported for the total synthesis of 190 [110][111][112][113][114] . A study on the constituents of the mangrove plant Lumnitzera racemosa produced two alkylphenols 191 and 192 [115] .…”
Section: Miscellaneousmentioning
confidence: 99%
“…Compound 7 was then demethylated by heating at 160 °C in the presence of MeMgI 9 to give (+)-bakuchiol (1) in good yield. The spectral data ( 1 H NMR, 13 C NMR, IR, EI-MS, [α] D ) 18 collected for the synthetic 1 were identical to those of the natural product.…”
Section: Scheme 1 Previous Total Synthesis Of (+)-Bakuchiol By Our Groupmentioning
confidence: 85%
“…Takano et al 10 reported the first enantiocontrolled total synthesis of (+)-bakuchiol (1) in 1990 in 11 steps from (S)-O-benzylglycidol. Following on from this work, Asaoka et al 11 (16 steps, in 1999), Li et al 12 (10 steps, in 2008), Novikov et al 13 (10 steps, in 2009) and Hoveyda et al 14 (3 steps, in 2010) have all succeeded in developing elegant enantioselective total syntheses of (+)-1. In our previous paper, 15 we reported the successful total synthesis of (+)-bakuchiol (1) in 14 steps from but-3-yn-1-ol based on the asymmetric 1,4-addition reaction of (H 2 C=CH) 2 Cu(CN)Li 2 to an α,β-unsaturated carboxylic acid derivative equipped with a chiral oxazolidinone auxiliary 2 for constructing the allcarbon chiral quaternary center 15 (Scheme 1).…”
mentioning
confidence: 85%
“…Earlier, we demonstrated the potential of this approach by converting the δ-sultone, obtained from (-)-citronellol by diazosulfonate C-H insertion, [2] to natural product bakuchiol. [7] We, thus, set out to explore preparation of other synthetic intermediates from common precursors using this reaction.…”
Section: Introductionmentioning
confidence: 99%